THE EFFECT OF FINANCIAL LITERACY, PERCEIVED USEFULNESS AND PERCEIVED EASE OF USE TO INTEREST IN USE INDONESIAN QUICK RESPONSE STANDARDS (QRIS) FOR CREATIVE INDUSTRY (MSMEs) IN SURAKARTA CITY - Octavianingrum, Putri Eka; Suprihati, Suprihati; Kusuma, Indra Lila (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
The purpose of this study is to determine the influence of variables related to research, namely, financial literacy, perceived usefulness and perceived ease of use on interest in using QRIS for creative industry players in Surakarta City. The data used is primary data obtained from the distribution of questionnaires using the Likert scale. The population in this study is creative industry players (MSMEs) in Surakarta City with a total of 3635 assisted MSMEs per 2021. This study used a purposive sampling method so that 100 samples of respondents were obtained. This study used multiple regression analysis methods in empirical testing and used the SPSS 25.0 application as its analysis tool. From the results of the analysis conducted, this study shows that financial literacy variables have a positive and significant influence on interest in using QRIS, which is 0.023 smaller than 0.05. The perceived usefulness variable has a significantly smaller value of 0.00 smaller than 0.05 and perceived ease of use also has a positive and significant effect on interest in using QRIS, which is 0.019 greater than 0.05 while the remaining 0.018 is influenced by other variables. Of these variables, perceived usefulness has the greatest influence on interest in using QRIS. Therefore, the more positive the perceived usefulness in using QRIS, the stronger the intention of MSMEs to use QRIS.